Logic, passion and the problem of convergence. Issue 3 (21st April 2017) - McShea, Daniel W.
Abstract : Our estimate of the likelihood of convergence on human-style intelligence depends on how we understand our various mental capacities. Here I revive David Hume's theory of motivation and action to argue that the most common understanding of the two conventionally recognized components of intelligence—reason and emotion—is confused. We say things like, 'Reason can overcome emotion', but to make this statement meaningful, we are forced to treat reason as a compound notion, as a forced and unhappy mixture of concepts that are incommensurate. An alternative is to parse intelligence in a different way, into two sets of capacities: (i) non-affective capacities, including logic, calculation and problem-solving; (ii) affective capacities, including wants, preferences and cares, along with the emotions. Thus, the question of convergence becomes two questions, one having to do with affective and one with non-affective capacities. What is the likelihood of convergence of these in non-human lineages, in other ecologies, on other worlds? Given certain assumptions, convergence of the non-affective capacities in thinking species seems likely, I argue, while convergence of the affective capacities seems much less likely.